Alcohol extract of Pterogyne nitens leaves fails to reduce severity of streptozotocin-induced diabetes in rats - de Souza, Aline [UNESP]; Vendramini, Regina C. [UNESP]; Brunetti, Iguatemy L. [UNESP]; Regasini, Luis O. [UNESP]; Siqueira Silva, Dulce H. [UNESP]; Bolzani, Vanderlan Silva [UNESP]; Pepato, Maria T. [UNESP] (My University, 2010)
Two constituents of Pterogyne nitens leaves, kaempferitrin, a diglycosylated flavonol, and galegin, a guanidine alkaloid, may be considered likely to exert an antidiabetic effect, on the basis of their chemical structures. Thus, experimentally diabetic rats were treated with P. nitens leaf extract, to observe the effects on biochemical and toxicological marker variables. Streptozotocin-diabetic rats (50 mg/kg body weight) were given ethanolic extract of the leaves (76 mg suspended in 0.5 mL of 10% aqueous glycerine per rat) (DP) by gavage, twice a day for 32 days. Diabetic controls were given 0.5 mL of 10% glycerine (DG), insulin (2.5 U in 0.3 mL s. c.) (DI) or 0.5 ml water (DW). Initial glycemia was 537.11 ± 10.35 mg/dL. Each week or fortnight after the treatment glucose, urea and protein contents were determined in the urine and glycemia and alkaline phosphatase activity in the serum. Except for proteinuria, the results for groups DP, DG and DW all differed significantly (p < 0.05) from those for group DI, which exhibited reduced values of all the other variables. The plant extract neither improved nor worsened the diabetic state of the rats; nor did it give rise to any hepato-biliary toxic effect. © 2010 Academic Journals.
Keywords: Alkaline phosphatase; Antidiabetic plant; Biochemical markers; Hepato-biliary toxicity marker